Ranolazine antagonizes catecholamine-induced dysfunction in isolated cardiomyocytes, but lacks long-term therapeutic effects in vivo in a mouse model of hypertrophic cardiomyopathy. (4th November 2015) - Flenner, Frederik; Friedrich, Felix W.; Ungeheuer, Nele; Christ, Torsten; Geertz, Birgit; Reischmann, Silke; Wagner, Stefan; Stathopoulou, Konstantina; Söhren, Klaus-Dieter; Weinberger, Florian; Schwedhelm, Edzard; Cuello, Friederike; et al.
Abstract: Aims: Hypertrophic cardiomyopathy (HCM) is often accompanied by increased myofilament Ca 2+ sensitivity and diastolic dysfunction. Recent findings indicate increased late Na + current density in human HCM cardiomyocytes. Since ranolazine has the potential to decrease myofilament Ca 2+ sensitivity and late Na + current, we investigated its effects in an Mybpc3 -targeted knock-in (KI) mouse model of HCM. Methods and results: Unloaded sarcomere shortening and Ca 2+ transients were measured in KI and wild-type (WT) cardiomyocytes. Measurements were performed at baseline (1 Hz) and under increased workload (30 nM isoprenaline (ISO), 5 Hz) in the absence or presence of 10 µM ranolazine. KI myocytes showed shorter diastolic sarcomere length at baseline, stronger inotropic response to ISO, and drastic drop of diastolic sarcomere length under increased workload. Ranolazine attenuated ISO responses in WT and KI cells and prevented workload-induced diastolic failure in KI. Late Na + current density was diminished and insensitive to ranolazine in KI cardiomyocytes. Ca 2+ sensitivity of skinned KI trabeculae was slightly decreased by ranolazine. Phosphorylation analysis of cAMP-dependent protein kinase A-target proteins and ISO concentration–response measurements on muscle strips indicated antagonism at β-adrenoceptors with 10 µM ranolazine shifting the ISO response by 0.6 log units. Six-month treatment with ranolazine (plasma level >20 µM) demonstrated a β-blocking effect, but did not reverse cardiac hypertrophy or dysfunction in KI mice. Conclusion: Ranolazine improved tolerance to high workload in mouse HCM cardiomyocytes, not by blocking late Na + current, but by antagonizing β-adrenergic stimulation and slightly desensitizing myofilaments to Ca 2+ . This effect did not translate in therapeutic efficacy in vivo .